A novel electrical depercolation model for stretchable nanocomposite strain sensors - Tomes, Oliver; Soul, Aaron; Zhang, Han; Bilotti, Emiliano; Papageorgiou, Dimitrios G (Nanoscale, 2024)
Flexible strain sensors have been subject to intense research efforts in recent years, in an attempt to overcome the limitations of their rigid counterparts and find use in demanding applications. In this work, the effective calibration of resistive-type, stretchable strain sensors is discussed. A new model for the piezoresistive response of stretchable polymer nanocomposite strain sensors is presented which facilitates calibration over the full conducting strain range of the material. This offers the potential to vastly improve the practical working range of sensors made using soft conductive nanocomposites, as well as to obtain key information towards improvement of sensing performance. The model has been successfully applied to multiple experimental measurements on silicone rubber (SR) nanocomposites reinforced with reduced graphene oxide (rGO) over a range of filler loadings. The effect of parameters such as filler dimensions, filler orientation and dispersion state is discussed, while predictions on sensitivity and working range are made on the basis of interparticle distance modelling. Our new piezoresistive model unleashes the full sensing potential of nanocomposites, enabling accurate calibration across the entire conducting strain range and establishing a new framework for exploring key insights into optimising performance.